Hubungan Tingkat Pengetahuan tentang Menstruasi dengan Kesiapan Menghadapi Menstruasi Pertama pada Siswi Kelas VI SDN Jakamulya V Bekasi Selatan - Fiah, Zahwa Alip; Futriani, Elfira Sri (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Adolescence is also known as puberty for early adolescents, namely the transition period from childhood to early adulthood where the first menstruation will occur. The average age for first menstruation in Indonesia is between 12-14 years. There are also some people who menstruate at the age of 9 but the population is still small. To find out the relationship between the level of knowledge about menstruation and readiness for the first menstruation in class VI students at SDN Jakamulya V South Bekasi in 2023. The method in this study used an analytic survey design with a cross sectional approach. From the results of the study of 40 respondents, the results obtained were less knowledge (50%), and readiness for the first menstruation, most of the respondents were in the unprepared category (85%). Then the P-Value = 0.018 < a = 0.05 then Ho is rejected and Ha is accepted. There is a significant relationship related to the level of knowledge and readiness for first menstruation in class VI students at SDN Jakamulya V South Bekasi. Keywords: Knowledge, Readiness for First Menstruation  ABSTRAK Masa remaja juga dikenal sebagai masa pubertas bagi remaja awal, yaitu masa transisi dari kanak-kanak menjadi dewasa awal dimana akan terjadi menstruasi pertama.  Usia menstruasi pertama di Indonesia rata-rata antara 12-14 tahun ada juga beberapa orang yang menstruasi pada usia 9 tahun tetapi masih sedikit populasinya. Untuk mengetahui hubungan tingkat pengetahuan tentang menstruasi dengan kesiapan menghadapi menstruasi pertama pada siswi kelas VI di SDN Jakamulya V Bekasi Selatan Tahun 2023. Penelitian ini menggunakan desain survey analitik, cross sectional. Hasil penelitian dari 40 responden, didapatkan hasil pengetahuan kurang (50%), dan kesiapan menghadapi menstruasi pertama sebagian besar responden dengan kategori tidak siap (85%). Maka didapatkan nilai P-Value = 0,018 < a = 0,05 maka Ho ditolak dan Ha diterima. Ada hubungan yang signifikan terkait tingkat pengetahuan dengan kesiapan menghadapi menstruasi pertama pada siswi kelas VI di SDN Jakamulya V Bekasi Selatan. Kata kunci: Pengetahuan, Kesiapan Menstruasi Pertama